Tanggalkan Khalifah di Bumi Ini: Membaca Narasi Sukarno Tentang Sekularisme Turki - Al Makin (IAIN Ponorogo, 2016)
Abstract: This article attempts to observe Sukarno’s article about the separation between religion and state” published in Panji Islam in 1940. Sukarno’s thought is still relevant to discuss up to now in Indonesian because some conservative and radical groups of Muslim have given the louder voices to the government demanding the system of caliphate state and rejecting free democracy by intimidation which ironically seemed to be given to these groups to rise. More than fifty years ago, Sukarno clearly argued that caliphate system of leadership in Muslim society was no longer relevant and even outdated. Sukarno took the case of Turkey, through which he hailed Mustafa Kemal Ataturk’s efforts in abolishing the outdated Ottoman caliphate in order to build the modern democracy of Turkey, which was able to address more real challenges facing Muslim society. Sukarno explained clearly that the separation of religion and state in Muslim society was needed to make the survival of both religion and state. He also presented history of Turkey in his argument that caliphate system of governing was not pure Islamic one, as it was an evolution of older system of government from the ancient Greco-Byzantium, in which religion played a vital role to legitimate the power of some emperors. Let alone, the history of Turkey had witnessed the weakening caliphate system of Ottoman in which religion and politics mingled so that Turkey was not able to control the vast Islamic territory, which ultimately its population rebelled the empire. Sukarno's reading and rhetoric in narrating Turkey was unique as he contextualized the Turkish history into Indonesian situation in the pre-independent period. Sukarno’s interpretation of Islam, history, and politics could serve as a foundation for those who sought the nature of religion and state relation and reminded those who recalled caliphate system during the reform era. Indeed, caliphate system has no place today in Indonesia as relentlessly told by Sukarno more than fifty years ago.الملخص: حاول هذا المقال إعادة القراءة لمقال كتبه سوكارنو في صحيفة